Review paper: gender competencies in the medical curriculum: addressing gender bias in medicine - Wong, Yut Lin (SAGE Publications, 2009)
Gender inequalities in health and gender bias in medicine are interrelated challenges facing health care providers and educators. Women and girls are disadvantaged in accessing health care because of their low social status and unequal treatment in medical care. Gender bias has long been inherent in clinical practice, medical research, and education. This can be traced to the medical curriculum that shapes the perceptions, attitudes, and behavior of the future doctor. The author advocates medical curricula change to address gender inequalities in health and gender bias in medicine. She analyses the reasons for integration of gender competencies in the medical curriculum, discusses what gender competencies are, and reviews ways to in-build gender competencies and their assessment. Efforts to change and gender sensitize medical curricula in developed and developing countries are also reviewed. The review hopes to contribute to strategic medical curriculum reform, which would lead to gender-sensitive health services and equity in health.